Blast resistance of membrane retrofit unreinforced masonry walls with flexible connections. Issue 4 (December 2017) - Gagnet, Eric M; Hoemann, John M; Davidson, James S
Unreinforced masonry infill walls are one of the most economical and widely used exterior wall systems. However, they can produce secondary fragments due to their brittle failure modes when subjected to an impulsive blast load. One retrofit to reinforce existing masonry walls is to install a membrane that prevents fragments from entering the building's interior. Previous research focused on defining the resistance provided by the wall membrane system, but did not include flexibility of the attachments and their influence on the retrofitted wall system. This article addresses that issue through (1) a review of existing membrane retrofit resistance definitions, (2) a derivation of the resistance definition that includes connection flexibility, (3) validation of the derived resistance definition through nonlinear finite element analyses, and (4) comparison of the resistance in a single-degree-of-freedom framework against full-scale blast testing.